Relatos de martirios misionales y la imagen de la mujer en Filipinas y Japón - Alabrús Iglesias, Rosa María (Cauriensia, 2023)
I In this work a comparative approach is made of the missions carried out in Asia by the various religious orders (Jesuits, Franciscans, Dominicans), in their different stages, through the stories of each order that, in many cases, have a character hagiographic and publicity nature of missionary work. After examining the various sources that supply this missionary discourse, information will be provided on the flow of martyrs in Japan that occurred especially in the first half of the seventeenth century, their hagiographic recognition and the little-known role of women in the missionary projection of the religious orders and in the own legacy of victims of martyrdom.